A New Approach to Constant Slope Surfaces with Quaternions. (18th March 2012) - Babaarslan, Murat; Yayli, Yusuf
Abstract : We show a new method to construct constant slope surfaces with quaternions. Moreover, we give some results and illustrate an interesting shape of constant slope surfaces by using Mathematica.